Comparison Between Electride Characteristics of Li3@B40 and Li3@C60 - Das, Prasenjit; Chattaraj, Pratim Kumar (Frontiers in Chemistry, 2021)
Density functional theory (DFT) based computation is performed on the endohedrally encapsulated Li3 cluster inside the B40 and C60 cages namely, Li3@B40 and Li3@C60. For both these systems, the Li-Li bond lengths are shorter than that in the free Li3 cluster. Due to confinement, the Li-Li vibrational frequencies increase in both the systems as compared to that in the free Li3 cluster. Thermodynamically, the formation of these two systems is spontaneous in nature as predicted by the negative values of Gibbs’ free energy changes (G). For both the systems one non-nuclear attractor (NNA) is present at the center of the Li3 cluster which is predicted and confirmed by the electron density analysis. The NNA population and the percentage localization of electron density at the NNA of the Li3@C60 system are higher than that in the Li3@B40 system. At the NNA the values of the Laplacian of electron density are negative and an electron localization function basin (ELF) is present at the center of the Li3 cluster for localized electrons. Both systems show large values of nonlinear optical properties (NLO). Both the Li3 encapsulated endohedral systems behave as electrides. Electrides have low work function and hence have a great potential in catalytic activity towards the activation of small molecules (such as CO2, N2). Even some electrides have greater catalytic activity than some well-studied metal-loaded catalysts. As the systems under study behave as electrides, they have the power to show catalytic activity and can be used in catalyzing the activation of small molecules.